Analysis of the Impact of Legal Consequences on the Intention and Behavior of Digital Platform Piracy in Indonesia - Edwinsa Auzan Hashfi; Arif Hartono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to test and analyze the impact of legal consequences on the intention to pirate digital products by integrating the legal consequence approach, ethics, and the Theory of Planned Behavior (TPB) to understand the practice of pirating digital products better. This study was conducted in Indonesia without being limited to a specific geographical area. The objects of research used are websites and platforms (such as Bolasiar.com, IndXXI, Spotify, Netflix, Video, Telegram, and the like). The population in this study is Indonesian people with various religious backgrounds who access websites or platforms from multiple sources to obtain digital products without a valid license. The data for this study are primary data from an online survey of 204 respondents. In practice, this study employs a convenience sampling technique administered to respondents via Google Forms, resulting in valid and reliable measurements. The type of SEM analysis used in this research is Partial Least Squares (PLS-SEM). The findings indicate that perceived likelihood of punishment, self-efficacy, and subjective norms have a positive influence on attitudes toward digital product piracy, whereas fear of legal consequences, attitudes toward piracy, and facilitating conditions do not have a significant effect on attitudes toward digital product piracy.